Envisioning Islamic Art and Architecture: Essays in Honor of Renata Holod - Roxburgh, David J. (Arts and Archaeology of the Islamic World, 2014)
Envisioning Islamic Art and Architecture: Essays in Honor of Renata Holod offers innovative analyses and interpretations of both familiar and previously unpublished objects and monuments, its essays adopting the broad range of methodological approaches stimulated by Holod's research and pedagogy.